PENGARUH DUA JENIS PAKAN KOMERSIAL DAN PAKAN RASIONAL TERHADAP PENAMPILAN AYAM KAMPUNG - Trisiwi, Harimurti Februari; Supartini, Nonok (BUANA SAINS, 2015)
The purpose of this study was to determine the effect of two commercial feed and feed the rational against the appearance of chicken. One hundred and twenty chickens unsexed placed randomly assigned to 3 treatment groups feed with four replications, each repeat of the three feed treatments, a commercial broiler starter feed (BR-I) production Japfa Comfeed Indonesia (P1), the commercial broiler starter feed (Br IA) Charoend production Pokphand Indonesia (P2), and a rational feed prepared with crude protein (CP) and metabolizable energy (ME) commercial feed (P3). Feed and water were given ad libitum. Data observed were feed intake, weight gain, feed conversion, protein consumption, balance efficiency of protein, and amino acid consumption. Data were analyzed by analysis of variance of a completely randomized design unidirectional pattern, if there are differences in test followed by Duncan Multiple Range Test. From the results of this study concluded that the two types of commercial diets produce feed intake and higher weight gain and feed conversion efficiency and balance of feed protein is better than rational